A DEMATEL-based approach of multi-criteria evaluation for urban fire and emergency facilities - Nyimbili, Penjani Hopkins; Erden, Turan; Mwanaumo, Erastus Misheng'u (Frontiers in Environmental Economics, 2023)
With the increasing complexity of rapidly growing urban environments and the interactions of humans and socioeconomic and political systems, the global urgency for applying sustainable risk management planning strategies, comprehensively for urban fire risk reduction activities, becomes increasingly evident in most fire-prone megacities worldwide such as Istanbul. The current research aims to examine the complex interrelationships and levels of influence among the criteria previously determined for optimally selecting new urban infrastructure for fire and emergency services in Istanbul as part of the fire risk mitigation planning efforts applying the multi-criteria decision analysis method of the Decision-Making Trial and Evaluation Laboratory (DEMATEL). Useful insights were generated from the study by constructing an intelligible structural model visually in the form of a digraph involving analysis of causal relationships among criteria and their directional influences, as well as corresponding degrees of strength. The findings reveal that high population density is the most critical criterion followed by the density of hazardous materials criterion in effectively planning new urban facilities for fire and emergency services, thus significantly influencing and impacting all the other criteria, while the distance-to-earthquake risk criterion does not influence any other criteria and consequently is not essential in the planning procedure. The DEMATEL model results were validated in terms of levels of criteria significance using previous studies and shown to be in high correlation. In this regard, these contextual relationships established would contribute toward an integrated fire risk mitigation planning policy formulation in urban environments through the engagement of all decision-makers across various backgrounds and disciplines such as urban and city planners, engineers, emergency and risk managers and administrators, socioeconomic and environmental experts, fire service industry practitioners, and local community leaders.